PENGARUH TEKNOLOGI INFORMASI DAN BUDAYA ORGANISASI TERHADAP KINERJA MANAJERIAL MELALUI MEDIASI SISTEM INFORMASI AKUNTANSI PADA CV. ANEKA ILMU SEMARANG - Mohklas . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
This research is aimed to know the influences of information technology, organizational culture and accountancy information system (AIS) toward the managerial working of branch office of CV. Aneka Ilmu Semarang. It also has an objective to identify which one is more give influence among information technology, organizational culture or accountancy information system toward the managerial working of branch office of CV. Aneka Ilmu Semarang.This research consists of four variables. In the first step, variable of information technology and organizational culture become free variable, while variable of accountancy information system become the bounded variable. Next, in the second step, the variable of information technology and organizational culture becomes free variable, SIA becomes mediation variable, while managerial working variable becomes bounded variable. The samples of the research are managers of the branch offices of CV. Aneka Ilmu Semarang (34 managers). The data compiled by questionaire wiil be validity and reliability tested and continued with path analysis.The result shows that information technology has positive influence toward accountancy information system (AIS) with the rate of significance 0,006 direct influence is 0,386. While organizational culture has positive influence toward accountancy information system (AIS) with the rate of significance 0,001 direct influence is 0,494. Information technology has positive influence toward managerial working with rate of significance 0,009, direct influence is 0,319. Organizational culture has positive influence with the rate of significance 0,005 direct influence 0,371 while accountancy information system (AIS) has positive influence toward managerial working with the rate of significance 0,353. Information technology has direct influence toward managerial working and indirect influence through characteristic of accountancy information system (AIS) 0,136, organizational culture has direct influence toward managerial working and indirect influence through characteristic of accountancy information system (AIS) 0,174.